Director's report of research in Kansas 2012 - Kansas State University. Agricultural Experiment Station (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2017)
This report contains the title, author, and publication information for manuscripts published by station scientists.
DRR12
Keywords: Kansas; Agricultural Experiment Station; Research; Publications; Finances; Projects